Inhibitory effect of coatings with different polymeric bases on germination and in vitro growth of anthracnose fungus - GOMES, Isamara Reis; SAMARÃO, Solange Silva; TAVEIRA, Gabriel Bonan; RODRIGUES, Pedro Souto; RESENDE, Eder Dutra de (Food Science and Technology, 2024)
Colletotrichum theobromicola is one of the fungus species that causes anthracnose in the papaya fruit. This study aimed to evaluate the effect of three polymeric bases in their usual concentrations – starch (6% m/v), carboxymethylcellulose (CMC, 1% m/v), and chitosan (2% m/v) – on the in vitro growth parameters of C. theobromicola: germination, conidia count, and membrane permeabilization, to identify a more suitable polymeric base to be applied in the development of an active coating for the postharvest conservation of papaya. In vitro growth was determined in Petri dishes for 7 days, while germination and membrane permeabilization were assessed after 24 h of incubation at 25 ± 3ºC. It was found that the different polymeric bases interfere with the germination and mycelial growth of C. theobromicola. The chitosan coating completely inhibited germination and in vitro growth of the fungus. Germination and in vitro growth were more easily achieved with the 6% starch coating. The 1% CMC also showed a high proportion of conidia germination but with a lower proportion of mycelial growth. Thus, based on the high cost of chitosan, CMC can be considered a more suitable polymeric base for the formulation of active coatings.